PROFESSIONAL VALUES IN A POLICE TRAINING CENTER IN THE NORTHEAST OF MEXICO - Farfán Mejía, Enrique (UNIVERSIDAD DE SONORA, 2023)
Abstract An investigation was developed, with a gender perspective, with the aim of knowing the students' perception of the professional values of cadets in police training. First, the professional values to be taught were identified in the study plan, then a questionnaire on these values was applied and, finally, the responses of the students by gender were compared.